Structural insights into the mechanism of rhodopsin phosphodiesterase - Tatsuya Ikuta (Nature Portfolio, 2020)
Rhodopsin phosphodiesterase (Rh-PDE) hydrolyzes both cAMP and cGMP in a light-dependent manner. Structural and functional analyses of the Rh-PDE from Salpingoeca rosetta reveal unusual rhodopsin topology comprising 8 transmembrane helices (TMs) and suggest that TM0 plays a crucial role in the enzymatic photoactivity.